Pengaruh Disiplin Kerja dan Loyalitas Terhadap Prestasi Karyawan Pada CV. Berkah Sukses Makmur - Asri Sanusi; Hasibuan, Siska (Jurnal Sains dan Teknologi, 2023)
This study serves to analyze the effect of work discipline and loyalty on the work performance of CV. Berkah Sukses Makmur employees. The population in this study was 40 permanent employees of the CV. Berkah Sukses Makmur. This study uses a quantitative method using a questionnaire. Data analysis in this study used the SPSS 24 program which included a validity test, reliability test, classical assumption test, multiple regression analysis, and hypothesis testing using the t-test and R2 test. The results of the analysis in the study showed that partially there was no effect of work discipline on work performance at the CV. Berkah Sukses Makmur. And partially there is the influence of loyalty to work performance at the CV. Berkah Sukses Makmur. From the results of data processing, simultaneously the independent variables affect the dependent variable. So it can be concluded that to improve employee performance, employee discipline and employee loyalty must also be improved.